Impact of Energy Transition Implications on Social Aspects of Surabaya City - Kania Salsabilah Nur Rifanda; Arie Dipareza Syafei; Rudi Rahmaddi (Jurnal Serambi Engineering, 2024)
Based on the latest data for 2022-2023, climate change-related natural disasters in Indonesia have increased quite significantly. Climate change is caused by high levels of greenhouse gases (GHG) accumulating in the atmosphere. Surabaya, the second largest city in Indonesia, contributes a high amount of GHG, while Indonesia has committed to efforts to reduce greenhouse gas emissions, which will result in a reduction of greenhouse gas emissions by 29% in 2030. Energy transformation is an alternative. It is important to support it, but society needs to prepare to implement the transition to a modern, reliable and low-carbon energy system globally. At least three factors are driving the energy transition: environmental, social and economic. Therefore, the research was carried out by analysing social impact projections using quantitative questionnaire methods. The energy transition has an impact on social aspects, as shown by the percentage of public acceptance of 75.11%. The level of acceptance by the people of Surabaya City regarding the impact of energy transformation is quite high with a percentage of 83.02%